Transformasi Teori Hukum Konstitusi dan Implikasinya dalam Kapita Selekta Hukum Tata Negara - Simajuntak, Reynold; Kurniawan, Girindra Wardhana (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
The transformation of constitutional law theory reflects a response to the political, social, and technological changes of modern times. This study aims to analyze how these transformations occur and their implications for constitutional law, particularly in Indonesia. Using a qualitative approach based on a literature review, this research highlights constitutional transformation through strengthening democracy, the application of digital technology, and the integration of environmental sustainability into legislation. The findings show that legal reform, which is more participatory and responsive, is essential to ensuring substantive justice. This transformation offers solutions to global challenges while strengthening the legitimacy of national constitutions.